PCBs and heavy metals in fish and shellfish, dietary exposure and neurobehavioral performance among Malaysian fishermen - Mohamad, Alina (2011)
Fish is a high-quality source of protein which also contains vitamins and other important nutrients, including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Polychlorinated biphenyls (PCBs) and heavy metals have the potential to accumulate in sediments as well as marine organisms, including in fish which can be transferred to human body via food chain. These contaminants are believed to be responsible for a wide variety of negative effects and may cause neurological and neurophysiological signs and symptoms. The main objectives of this study was to determine the type and amount of contaminants (PCBs and heavy metals) in fish and shellfish, its dietary exposure and neurobehavioral performance among fishermen along Straits of Malacca. The association between level of exposure and neurobehavioral performance were also determined.PCBs were prepared and analyzed using method defined by US EPA (Method 1613). For determination of heavy metals, the sample was prepared using method from Falco, et al., (2006). For dietary intakes, the fishermen were measured using Food Frequency Questionnaire (FFQ). The highest amount of PCBs was in cockles with 2.61 pg/g wet weight while Indian mackerel showed a concentration of 1.37 pg/g wet weight for fish species. For mercury, the highest amount was in Long-tailed butterfly ray at 0.0163 ± 0.000 μg/g wet sample. It can be concluded that fish and shellfish caught along the Straits of Malacca are safe to consume in terms of PCBs and heavy metals level. For dietary exposure study, 90 fishermen participated in the study. The mean exposure to PCBs was 2.77 ± 0.261 pg/ kg bw/ day. The highest mean exposure for heavy metals was arsenic at 4.517 ± 0.400 μg/ kg bw/ day. This study found that the PCBs and heavy metals exposures via dietary intake of fish and shellfish were within tolerable daily intake. Results of Neurobehavioral Core Test Batery (NCTB) showed that 97 % of respondents achieved high score (>30) which mean the neurobehavioral performance was not affected. There were no correlations between dietary exposure of contaminants and neurobehavioral performance among fishermen. As a conclusion, dietary exposure to PCBs and the selected heavy metals via fish consumption was not sufficient to cause neurobehavioral changes among fishermen. Data obtained from the present study can be used as preliminary information on levels and types of contaminants in fish and shellfish besides the dietary exposure related to intake of the fish and shellfish. Although the level of exposure was low, there is a potential to be higher in the future. Therefore, further investigation is needed for monitoring of these contaminants in food, especially fish and shellfish.